2023
DOI: 10.3390/rs15061510
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Improvement of Aerosol Optical Depth from CHIMERE Simulations Using MODIS Satellite Observations

Abstract: We present a supervised machine learning (ML) approach to improve the accuracy of the regional horizontal distribution of the aerosol optical depth (AOD) simulated by the CHIMERE chemistry transport model over North Africa and the Arabian Peninsula using Moderate Resolution Imaging Spectroradiometer (MODIS) AOD satellite observations. Our method produces daily AOD maps with enhanced precision and full spatial domain coverage, which is particularly relevant for regions with a high aerosol abundance, such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The advanced Himawari instrument was again revised by the deep learning technique, which reduced the noise at the lower NDVI for a short‐wave infrared channel. A recent study by Lemmouchi et al (2023) found remarkable reduction in biases in the extreme shits of AOD in an aerosol‐rich area such as the Sahara Desert. They incorporated chemical transport models for accuracy and later indicated that models like RF and XGB artificial networks had few spatial artefacts and regression models had overcome the errors and reduced the biases, suggesting that ML and AI can be used for improvising statistical linear correlations.…”
Section: Discussionmentioning
confidence: 96%
“…The advanced Himawari instrument was again revised by the deep learning technique, which reduced the noise at the lower NDVI for a short‐wave infrared channel. A recent study by Lemmouchi et al (2023) found remarkable reduction in biases in the extreme shits of AOD in an aerosol‐rich area such as the Sahara Desert. They incorporated chemical transport models for accuracy and later indicated that models like RF and XGB artificial networks had few spatial artefacts and regression models had overcome the errors and reduced the biases, suggesting that ML and AI can be used for improvising statistical linear correlations.…”
Section: Discussionmentioning
confidence: 96%